Exergoeconomic optimisation of an air cooled heat exchanger with copper oxide nanoparticles - Javani, Nader (INDERSCIENCE ENTERPRISES LTD, 2019)
In the current study, the effect of suspended CuO nanoparticles in a fluid on the exergoeconomic and thermoeconomic properties of an air-cooled heat exchanger (ACHE) is investigated. Particle swarm optimisation algorithm is employed for multi-objective optimisation where the exergy efficiency and effectiveness versus total annual cost (TAC) are considered as two sets of objective functions for exergoeconomic and thermoeconomic optimisation, respectively. For both cases, the results are compared with the base fluid, which has no nanoparticles. Results show that nanoparticles have no meaningful effect on the exergoeconomic improvement of ACHE while a significant improvement is observed for the thermoeconomic optimisation. Also, it is shown that CuO nanoparticle added into the base fluid can decreases the heat exchanger total annual cost and increase the heat exchanger effectiveness.
Keywords: air cooled heat exchanger; ACHE; exergoeconomic; nanoparticle; exergy efficiency; optimisation; MULTIOBJECTIVE OPTIMIZATION; FLAT-PLATE; NANOFLUIDS; ENHANCEMENT; COOLANT; SYSTEM; Thermodynamics; Energy & Fuels